(untitled) (International Seven Journal of Multidisciplinary, 2025)
AI-powered marketing automation has deeply transformed e-commerce strategies, offering more personalized and efficient campaigns. AI enables more precise consumer segmentation and enhances the customer experience through technologies such as chatbots, virtual assistants, and targeted product recommendations. Additionally, machine learning and natural language processing tools allow businesses to execute real-time marketing, quickly adjusting to consumer behaviors and needs. However, the implementation of AI requires a careful approach, with special attention to data privacy and algorithm transparency. Companies must ensure compliance with regulations such as LGPD (General Data Protection Law) and GDPR (General Data Protection Regulation) to avoid legal risks. Nevertheless, businesses that integrate AI into their marketing operations gain a significant competitive advantage, driving higher engagement, increasing conversion rates, and fostering long-term consumer loyalty. To ensure successful implementation, it is essential to balance innovation with ethical responsibility, preventing excessive personalization from violating user privacy. The research cited in the text highlights the challenges and opportunities of AI-based marketing automation, suggesting that when applied strategically and ethically, AI can enhance both the customer experience and drive sustainable growth for companies in the digital marketplace.